2016
DOI: 10.1093/pubmed/fdw026
|View full text |Cite
|
Sign up to set email alerts
|

Food safety behaviors observed in celebrity chefs across a variety of programs

Abstract: This study suggests that there is a need for improvement in demonstrated and communicated food safety behaviors among professional chefs. It also suggests that public health professionals must work to mitigate the impact of poorly modeled behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 27 publications
5
38
0
Order By: Relevance
“…Lack of meat thermometers usage was reported to be a common behavior among celebrity chefs. A content analysis of 100 US TV shows by Maughan, Chambers, and Godwin (2017) showed that 75% of the shows did not use a meat thermometer or give temperature information for different types of meat. Similar results were reported by Woods (2015) based on 60 TV cooking shows in the US.…”
Section: Usage Of Meat Thermometers On Tv Showsmentioning
confidence: 99%
“…Lack of meat thermometers usage was reported to be a common behavior among celebrity chefs. A content analysis of 100 US TV shows by Maughan, Chambers, and Godwin (2017) showed that 75% of the shows did not use a meat thermometer or give temperature information for different types of meat. Similar results were reported by Woods (2015) based on 60 TV cooking shows in the US.…”
Section: Usage Of Meat Thermometers On Tv Showsmentioning
confidence: 99%
“…Hygiene lapses were assessed with a self‐developed scoring sheet listing common violations of basic hygiene rules (see the Supporting Information). The scoring sheet was based on hygiene lapses previously observed in the context of TV cooking shows (Borda et al., 2014; Geppert et al., 2019; Maughan et al., 2017) and covered the key areas for safe food handling identified by the WHO (2006): keep clean, separate raw and cooked, cook thoroughly, keep food at safe temperatures (WHO also recommends to use safe water and raw materials, which was treated as a given in the context of our study). A draft version of the scoring sheet was reviewed by external experts in the field of food hygiene who were not involved in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Analogously to the development of the scoring sheet (see above), the hygiene behavior demonstrated in the videos was based on previous findings pertaining to the adherence to hygiene rules in TV cooking shows (Borda et al., 2014; Geppert et al., 2019; Maughan et al., 2017). Common mistakes observed on TV include poor hand hygiene, such as a lack of hand washing before starting food preparation, after handling raw food and after coughing, scratching or blowing one's nose; insufficient cleaning of utensils and surfaces between operations; as well as personal hygiene aspects such as wearing rings during food preparation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations